Detection of infectious bursal disease virus using SYBR Green 1 based realtime polymerase chain reaction - Hamzah, Hairul Aini; Omar, Abdul Rahman; Bejo, Mohd Hair; Ideris, Aini (Penerbit Universiti Sains Malaysia, 2004)
Infectious bursal disease (IBD) is an acute contagious viral disease of young chickens known as Gumboro disease (Lasher and Shane, 1994). The etiological agent, IBD virus (IBDV), has a predilection for the cells of the bursa of Fabricius where the virus infects lymphocytes of the B-cell lineage (Burkhardt et al., 1987).